1993
DOI: 10.1113/jphysiol.1993.sp019496
|View full text |Cite
|
Sign up to set email alerts
|

Relaxant innervation of the guinea‐pig trachealis: demonstration of capsaicin‐sensitive and ‐insensitive vagal pathways.

Abstract: SUMMARY1. The guinea-pig trachea was isolated with its extrinsic innervation intact and placed in a water-jacketed dissecting dish containing warmed, oxygenated Krebs solution. The trachea was not separated from the oesophagus. Two adjacent cartilage rings of the rostral portion of the trachea were cut open opposite the trachealis and prepared for isometric tension measurements.2. Following the addition of atropine and contraction of the trachealis with prostaglandin F2a (PGF2.), stimulation of the cervical sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
46
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(52 citation statements)
references
References 25 publications
(47 reference statements)
6
46
0
Order By: Relevance
“…The trachea and oesophagus of each animal were isolated with their extrinsic innervation intact and pinned dorsal-side down to the bottom of a water-jacketed dissecting dish continuously overfilled (20 ml min-') with warmed (37°C), oxygenated Krebs solution of the following composition (mM): NaCl, 118; KCl, 5-4; NaH2PO4, 1; MgSO4, 1 2; CaCl2, 1-9; NaHCO3, 25; dextrose, 11-1. In some preparations two adjacent cartilage rings of the rostral trachea (rings 6 and 7 caudal to the larynx) were cut open opposite the trachealis and prepared for isometric tension measurements (see Canning & Undem, 1993a). In other preparations, isometric tension was measured in a rostral segment of intact tracheal tubes as previously described (Canning & Undem, 1993b).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The trachea and oesophagus of each animal were isolated with their extrinsic innervation intact and pinned dorsal-side down to the bottom of a water-jacketed dissecting dish continuously overfilled (20 ml min-') with warmed (37°C), oxygenated Krebs solution of the following composition (mM): NaCl, 118; KCl, 5-4; NaH2PO4, 1; MgSO4, 1 2; CaCl2, 1-9; NaHCO3, 25; dextrose, 11-1. In some preparations two adjacent cartilage rings of the rostral trachea (rings 6 and 7 caudal to the larynx) were cut open opposite the trachealis and prepared for isometric tension measurements (see Canning & Undem, 1993a). In other preparations, isometric tension was measured in a rostral segment of intact tracheal tubes as previously described (Canning & Undem, 1993b).…”
Section: Methodsmentioning
confidence: 99%
“…We previously reported that the capsaicin-sensitive fibres mediating NANC relaxations of the trachealis are carried by the superior laryngeal nerves (Canning & Undem, 1993a). Accordingly, this pathway (which we will henceforth call the capsaicin-sensitive vagal pathway) was selectively stimulated by cutting the vagus nerves caudal to the nodose ganglia and stimulating them bilaterally rostral to the ganglia with suction electrodes (World Precision Instruments, Sarasota, FL, USA).…”
Section: Nerve Stimulationmentioning
confidence: 99%
See 3 more Smart Citations